Why poor children are more likely to become poor readers: The school years. (November 2013) - Buckingham, Jennifer; Wheldall, Kevin; Beaman-Wheldall, Robyn
Socioeconomic status at the individual- and school-level are positively related to literacy achievement in all English-speaking countries. The components of socioeconomic status – income, parent education and parent occupation – are each statistically significant predictors of school literacy achievement but they are primarily a proxy for more directly salient factors. This literature review outlines the factors that are most strongly implicated in literacy achievement. At the individual-level, they are early literacy ability, gene–environment interactions, home learning environment, time spent reading, sleep, school attendance and school mobility. At the school-level, they are school practices and teacher quality, including quality of initial reading instruction. These factors are interactive; not only are socioeconomically disadvantaged children more likely to experience these conditions, they are also more adversely affected by them than their more advantaged peers. This review concludes that understanding the nature of the relationship between socioeconomic status and literacy is the key to mitigating it.